Facing legal barriers regarding disclosure of genetic information to relatives. Issue 4 (1st October 2020) - Gilbar, Roy; Barnoy, Sivia
Abstract : Leading research projects are evidence of the growing public interest in genetic diagnosis and treatment. In this context, disclosure of genetic information to relatives has become a prominent issue. However, this involves patient confidentiality, which is grounded in law and conflicts with disclosure to relatives. When conducting a legal and bioethical discussion in this context, it is first necessary to examine how clinicians perceive the role of law in their practice and how they interpret it. A qualitative study was therefore conducted among clinicians in Israel. The findings indicate that the clinicians' approach is more relational than that of the law, in view of their pro-active steps to ensure that familial information reaches the relatives when the patient is reluctant to convey this information themselves. In light of these findings the authors argue that the law can resolve situations of explicit and implicit refusal to inform relatives.